Manajemen Pesantren dalam Meningkatkan Mutu Pendidikan Pondok Pesantren Berbasis Kemandirian Santri di Pondok Putri Pusat Zainul Hasan Genggong Probolinggo - Khoirun Nisa; Ismatul Izzah; Mohammad Ahyar Ma'arif (Transformasi Manageria Journal of Islamic Education Management, 2025)
This study discusses the management of Islamic boarding schools in improving the quality of education with an approach based on student independence. The management applied includes planning, organizing, implementing, and evaluating which aims to empower students to be independent in the learning process and life of the Islamic boarding school. The approach to student independence is considered a key factor in improving the quality of education in Islamic boarding schools as a whole, because independence encourages responsibility, discipline, and motivation to learn in students. The research method used is a qualitative descriptive method with a case study approach. Data were obtained through in-depth interviews, observation, and documentation. Data analysis techniques use the interactive Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that effective management and the implementation of student independence can synergistically improve the quality of education, produce quality graduates in terms of both religion and academics, and be able to compete in the modern era without eliminating the values of the Islamic boarding school. Supporting factors for the success of this management include the leadership of the caretaker, the active role of teachers, and the involvement of students in managing the Islamic boarding school. Conversely, obstacles such as lack of awareness of administrators and teachers in carrying out their duties can hinder quality improvement. Therefore, the management of the quality of Islamic boarding school education needs to be formulated and implemented carefully so that the goal of improving the quality of education based on the independence of students can be achieved optimally.